2021
DOI: 10.1021/acssuschemeng.0c08009
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell-Structured ZIF-8@PDA-HA with Controllable Zinc Ion Release and Superior Bioactivity for Improving a Poly-l-lactic Acid Scaffold

Abstract: Zeolitic imidazolate framework-8 (ZIF-8) nanoparticles are able to act as effective reinforcements to enhance the overall performance of a poly-l-lactic acid (PLLA) scaffold due to its interface compatibility and natural degradability. Nevertheless, the fast degradation of ZIF-8 would release excessive zinc ions, which produces adverse effects on natural cell growth. In this study, a core–shell-structured nanoparticle, in which ZIF served as a core and hydroxyapatite (HA) served as a shell, was constructed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 58 publications
(91 reference statements)
1
31
0
Order By: Relevance
“…Meanwhile, a peak related to –SH appeared at 2521 cm −1 [ 33 ], which demonstrated that L-cysteine-grafted alginate (ALG-SH) was successfully prepared. Wide absorption bands around 3450 cm −1 , 1641 cm −1 , 1397 cm −1 in the spectra of CNT were attributed to the stretching vibration of –OH, C=O and the bending vibration of –OH from the carboxyl group in CNT [ 34 ], respectively. However, new absorption peaks appeared at 1544 cm −1 and 1453 cm −1 in the spectra of CNT@PDA and CNT@ALG, which were attributed to the bending vibration of N–H and the bending vibration of –CH 2 –; furthermore, the weak peak at 2521 cm −1 decreased in the spectrum of CNT@ALG, meaning that the –SH group did not exist in CNT@ALG, implying that the –SH group reacted with the quinone group and formed C–S covalent bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a peak related to –SH appeared at 2521 cm −1 [ 33 ], which demonstrated that L-cysteine-grafted alginate (ALG-SH) was successfully prepared. Wide absorption bands around 3450 cm −1 , 1641 cm −1 , 1397 cm −1 in the spectra of CNT were attributed to the stretching vibration of –OH, C=O and the bending vibration of –OH from the carboxyl group in CNT [ 34 ], respectively. However, new absorption peaks appeared at 1544 cm −1 and 1453 cm −1 in the spectra of CNT@PDA and CNT@ALG, which were attributed to the bending vibration of N–H and the bending vibration of –CH 2 –; furthermore, the weak peak at 2521 cm −1 decreased in the spectrum of CNT@ALG, meaning that the –SH group did not exist in CNT@ALG, implying that the –SH group reacted with the quinone group and formed C–S covalent bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Ti has a higher Young's modulus than bone, [ 10,11 ] is chemically different from bone mineral, and causes interference with imaging. [ 12,13 ] H‐Ap has been used as a standard orthopaedic material for decades [ 14 ] but limitations, such as, low resorbability and contribution to the requirement of revision surgery have been reported. [ 15–17 ] Nanocrystalline carbonate‐rich hydroxyapatite (C‐Ap) potentially addresses the issues with Ti and H‐Ap.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these research efforts, PLA is used today in a wide variety of applications [ 18 , 19 , 20 ]. In order to increase the competitiveness of biodegradable composite materials in such a way that they can displace conventional non-biodegradable materials in very dynamic and demanding sectors such as packaging, construction, textiles, and the automotive industry, a new generation of hierarchical or multiscale biodegradable composite materials (HBC) containing micro- and nanosized mechanical reinforcements are currently being developed [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%